case report Intramuscular hemangioma: a rare case of hemangioma in biceps muscle - KAREEM, TARA FAROOQ; Fakhri, Rasha Thameen; MUHI, AHMED MURAD (Journal of the Faculty of Medicine Baghdad, 2019)
Intramuscular hemangiomas are rare asymptomatic angiomatous tumors , showing a slow growing pattern . We reported a rare case of biceps muscle hemangioma  in a 22-years-old man who presented with progressive swelling following a simple trauma four years ago , after examining the patient with ultrasound (US) ,computed tomography( CT) scan and magnetic resonance imaging (MRI), which was confirmed by histopathology later on .